Implementasi Peraturan Daerah Kabupaten Lampung Selatan Nomor 2 Tahun 2015 Tentang Pengelolaan Sampah Desa Banjar Agung Perspektif Siyasah Tanfidziyyah - Lia Dwi Safitri; Fathul Mu'in; Rudi Santoso (Kartika: Jurnal Studi Keislaman, 2026)
The issue of waste management in Indonesia has become increasingly complex due to population growth, urbanization, and changing consumption patterns. Similar conditions occur in Banjar Agung Village, Jati Agung District, South Lampung Regency, where low public awareness, limited infrastructure, and weak supervision continue to hinder the implementation of waste management policies. This study aims to analyze the implementation of South Lampung Regency Regional Regulation Number 2 of 2015 concerning Waste Management and examine it from the perspective of fiqh siyasah tanfidziyyah. This research employed a qualitative field research approach. Data were collected through observation, interviews, and documentation involving village officials, waste management officers, community leaders, and local residents. Data analysis used the Miles, Huberman, and Saldaña interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the implementation of the regional regulation has not been optimal due to weak policy communication, limited resources, low community participation, and the absence of an integrated waste management system. From the perspective of fiqh siyasah tanfidziyyah, the policy implementation has not fully reflected the principles of amanah, maslahah, ‘adl, and prevention of mafsadah. Therefore, institutional strengthening, environmental education based on Islamic values, and greater community participation are necessary to create sustainable waste management